Exploring diet-induced ketosis with exogenous ketone supplementation as a potential intervention in post-traumatic stress disorder: a feasibility study - Edwards, Maria G. P.; Furuholmen-Jenssen, Tobias; Søegaard, Erik Ganesh Iyer; Thapa, Suraj Bahadur; Andersen, Jens R. (Frontiers in Nutrition, 2024)
Background: Post-Traumatic Stress Disorder (PTSD) is a severe and pervasive mental disorder, and patients experience numerous distressing symptoms and impairments that significantly impact their lives. In addition to being a mental disorder, PTSD is strongly associated with a wide range of metabolic abnormalities that affect the entire body. Existing treatment options of psychotherapy and medications are often ineffective. Exploring other potential treatments is necessitated. The ketogenic diet has shown potential as a metabolic therapy in certain neurological and mental disorders and is a promising intervention in the treatment of PTSD.Aim: This study aimed to examine if a 4-week ketogenic diet intervention supplemented with exogenous ketones was feasible in adult patients with PTSD, to what extent it was possible to recruit patients, attain and maintain ketosis, the occurrence of serious adverse reactions and adverse reactions to KD-KS, and acceptance of treatment. Our exploratory aims were changes in PTSD symptoms and health-related quality of life (QoL) from baseline to 4 weeks.Methods: Patients 18 £ 65 years old, diagnosed with PTSD, and receiving outpatient treatment for